Synthesis and performance of experimental resin-based dental adhesives reinforced with functionalized graphene and hydroxyapatite fillers. (September 2022) - Ilie, Nicoleta; Erich Serfözö, Norbert; Prodan, Doina; Diegelmann, Julia; Moldovan, Marioara
Graphical abstract: Highlights: Nano-powders of functionalized graphene and hydroxyapatite were synthesized. Novel, non-toxic dental adhesives were formulated. In-vitro performance under clinically relevant environmental conditions and aging enables clinical use. Abstract: Functionalized graphene and hydroxyapatite fillers are proposed as reinforcing particles in light-cured adhesives for dental applications. Silica-silver-graphene (SiO2 -Ag-Gr), silver-doped hydroxyapatite (HA-Ag), graphene and silver doped hydroxyapatite (HA-Ag-Gr), and regular silica (SiO2 ) as inorganic powders, together with bis-GMA (2, 2-bis[4-(2-hydroxy-3-methacryloxypropoxy) oligomers, as main components of the organic matrix, were synthesized. Light field transmission electron microscopy and electron diffraction proved the successful synthesis of the powders. The experimental adhesives showed a positive influence on local biocompatibility up to 6 months in an in-vitro simulation of clinically relevant environmental conditions and aging. Bonding to human dentin reveal a particular fracture pattern with preferential adhesion to the restorative material in contrast to the gold standard adhesive used as reference, which adheres preferentially to the tooth structure. Bond strength was slightly lower, initial bond reliability slightly improved, and the morphology of interaction with tooth structure similar to the reference. Functionalized graphene and hydroxyapatite fillers in dental adhesives have demonstrated their potential for use in dental applications.